Copper and cobalt deficiencies in cattle and sheep in Northeastern and Northern Brazil - Tokarnia, Carlos Hubinger; Canella, Camillo F. C.; Guimarães, Jorge Almeida; Döbereiner, Jürgen (Pesquisa Agropecuaria Brasileira, 2014)
The results of chemical analyses of liver samples of cattle and sheep collected in the Northeast and North of Brazil are given. These results are grouped according to the region of origin. From some of these regions histories of diseases probably caused by mineral deficiencies are given, together with an interpretation of the analytical data and results of other studies made. For a better understanding of the conditions in the different regions there are included, in the Tables as well as in the interpretation of the results of analyses, data already published by the authors. The studies show that there is a severe copper deficiency on the "Costa do Piauí" (coast of Piauí) and the "Ilha de Marajó" (Island of Marajó). In addition deficient and subdeficient values in copper were found in liver samples collected in the "Sertão Nordestino" (northeastern savannahland), "Interior do Piauí" (hinterland of Piauí), "Chapadas do Maranhão" (higher areas of Maranhão). "Serra da Ibiapaba" (moutain range of Ibiapaba) in the region of sugar cane plantation and of "carrasco", Ceará, in the Região Litorânea do Nordeste" (coastal area of the Northeast), Ceará, in the "Território do Rio Branco" (Territory of Rio Branco, today Roraima) and the "Ilha de São Luiz" (Island of São Luiz), Maranhão. Severe cobalt deficiency was found in the "Serra da Ibiapaba", region of sugar cane plantation, Ceará. Deficient and subdeficient values in cobalt were found in liver samples collected in the region of the “Chapadas do Maranhão", "Território do Rio Branco", "Costa do Piauí" and the region "Interior do Piauí".